Outstanding scientific paper award for her research - Reyes, Melissa L. (Animo Repository, 2002)
Psychology faculty Dr. Melissa Reyes received the Outstanding Scientific Paper Award for her research, Differential Effects of Mathematical Ability and Language Use on Computational and Conceptual Knowledge of Descriptive Statistics, published in The Asia-Pacific Education Researcher, (9)1, by the DLSU Press during the 24th Annual Scientific Meeting of the NAST.